Diabetic Retinopathy and Its Risk Factors in a Population-Based Study - Masil George MD; Richard Harper MD; Appathurai Balamurugan MD, MPH; Greta Kilmer MS; LaTonya Bynum BS (SAGE Publishing, 2011)
Aim : To assess the prevalence of diabetic retinopathy and its risk factors among people with diabetes using a population-based survey and discuss strategies that can be used to both prevent and manage diabetes-related complications in a primary care setting. Methods : The prevalence of self-reported doctor-diagnosed diabetic retinopathy and its risk factors were estimated using data from the Arkansas Behavioral Risk Factor Survey, 2003-2007. Five years of survey data were combined and weighted to the population to assess the risk factors that predict the prevalence of diabetic retinopathy. The study involved 2477 people who reported that they have been diagnosed with diabetes. Results : Twenty-two percent of survey respondents with diabetes had been diagnosed with diabetic retinopathy. Using a multivariate adjusted model, blacks (odds ratio [OR] = 1.76, 95% confidence interval [CI], 1.26, 2.45), those with some high school education (OR = 2.78, 95% CI, 1.80, 4.28), people with diabetes for more than 10 years (OR = 2.14, 95% CI 1.61, 2.85), people on insulin treatment (OR = 2.35, 95% CI 1.78, 3.08), those who had taken a course to manage their diabetes (OR = 1.54, 95% CI 1.20, 1.99), and those with chronic foot ulcers (OR = 2.24, 95% CI 1.62, 3.09) were more likely to have been diagnosed with diabetic retinopathy. Conclusions : The prevalence of diabetic retinopathy and its risk factors are evident. Novel approaches to increase the screening and treatment of these frequent complications are key to optimize diabetes care.